Synthesis and Spectral Investigations of 2,5,7-Triaryl-5H-[1,3,4]thiadiazolo[3,2-a]pyrimidin-6[7H]-ones - Koparir, Metin; Cansiz, Ahmet; Cetin, Ahmet (Asian Journal of Chemistry, 2016)
A general and convenient route for the synthesis of 5-(aryl)-[1,3,4]thiadiazol-2-ylamines (2a–d), Schiff bases of thiadiazoles (3a–p) and 2,5,7-triaryl-5H-[1,3,4]thiadiazolo[3,2-a]pyrimidin-6[7H]-one (4a–p) is reported. The characterizations of these compounds were obtained by elemental analyses, IR, 13C and 1H NMR techniques.